Pre-assessments of optical transition, gain performance and temperature sensing of Er3+ in NaLn(MoO4)2 (Ln = Y, La, Gd and Lu) single crystals by using their powder-formed samples derived from traditional solid state reaction. (August 2021) - Sha, Xuezhu; Chen, Baojiu; Zhang, Xizhen; Zhang, Jinsu; Xu, Sai; Li, Xiangping; Sun, Jiashi; Zhang, Yuhang; Wang, Xin; Zhang, Yanqiu; Wang, Li; Hua, Ruinian
Highlight: A route for pre-assessing the rare earth doped laser crystals is established. Optical and laser performance for NaLn(MoO4 )2 :Er 3+ (Ln = Y, La, Gd and Lu) is assessed. Temperature sensing for for NaLn(MoO4 )2 :Er 3+ (Ln = Y, La, Gd and Lu) is compared. Abstract: Rare earth doped molybdate single crystals are excellent laser working media. The growths of molybdate single crystals are money-cost and time-consuming. It would be preferable if the spectroscopic properties and laser performance of the laser crystals could be pre-assessed before their growths. In this work, we proposed a route to pre-assess the spectroscopic properties, gain performance and temperature sensing effects for the rare earth doped molybdate single crystals by using the powder-formed rare earth doped molybdate phosphors. The route we proposed was applied for assessing the Er 3+ doped NaLn(MoO4 )2 (Ln = Y, La, Gd and Lu) crystals by using the corresponding molybdate phosphors which were prepared via a solid state reaction. The optical transition properties of Er 3+ in these molybdates were studied in the framework of Judd-Ofelt theory by using the diffuse-diffraction spectra. The radiative transition rates, fluorescence branching ratios and radiative lifetimes were further confirmed and compared for all studied Er 3+ doped molybdates. Furthermore, the absorption cross sections, emission cross sections and optical gain coefficient spectra for the interested transitions of Er 3+ in the molybdates were also determined via Füchtbauer-Ladenburg formula and McCumber theory. Meanwhile, the laser gain performance for the studied molybdate laser crystals was also assessed and compared with each other. A route for advanced heat management for the laser devices was proposed as well, and the temperature detection performance of the molybdates was also evaluated. This study proves that the pre-assessments for the rare earths doped laser single crystals by using their corresponding easy-prepared phosphors are workable.